Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4cp03343d
|View full text |Cite
|
Sign up to set email alerts
|

Noble-metal-free BODIPY–cobaloxime photocatalysts for visible-light-driven hydrogen production

Abstract: In this study a series of supramolecular BODIPY-cobaloxime systems Co-Bn (n = 1-4): [{Co(dmgH)2Cl}{4,4-difluoro-8-(4-pyridyl)-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene}] (Co-B1), [{Co(dmgH)2Cl}{4,4-difluoro-8-(4-pyridyl)-1,3,5,7-tetramethyl-2,6-diiodo-4-bora-3a,4a-diaza-s-indacene}] (Co-B2), [{Co(dmgH)2Cl}{4,4-difluoro-8-(3-pyridyl)-1,3,5,7-tetramethyl-4-bora-3a,4a-diaza-s-indacene}] (Co-B3), and [{Co(dmgH)2Cl}{4,4-difluoro-8-(3-pyridyl)-1,3,5,7-tetramethyl-2,6-diiodo-4-bora-3a,4a-diaza-s-indacene}] (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 50 publications
6
43
0
Order By: Relevance
“…This suggests the necessity of a strong intersystem crossing (ISC) to form a long-lived, high-yield triplet excited state for efficient photocatalysis. Further evidence for the important role of a triplet excited state was reported by the groups of Weare and Luo for intermolecular [16], as well as intramolecular [13,[15][16][17] BODIPY-cobaloxime systems. More recently, Eisenberg et al have used a combination of strongly light-absorbing BODIPYs and platinum diamine dithiolate charge transfer chromophores for sensitizing TiO2 in light-driven reduction of aqueous protons [18,19].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…This suggests the necessity of a strong intersystem crossing (ISC) to form a long-lived, high-yield triplet excited state for efficient photocatalysis. Further evidence for the important role of a triplet excited state was reported by the groups of Weare and Luo for intermolecular [16], as well as intramolecular [13,[15][16][17] BODIPY-cobaloxime systems. More recently, Eisenberg et al have used a combination of strongly light-absorbing BODIPYs and platinum diamine dithiolate charge transfer chromophores for sensitizing TiO2 in light-driven reduction of aqueous protons [18,19].…”
Section: Introductionmentioning
confidence: 87%
“…Recent developments include the implementation of non-noble metal components, or even metal-free compounds into these systems and several groups described the use of classical organic dyes, such as Fluorescein, dyes, such as Fluorescein, porphyrins, or Eosin Y, as photosensitizer species [4][5][6][7][8][9][10][11]. Moreover, in recent years, BODIPY (boron dipyrromethene; IUPAC name: 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene) dyes have also attracted considerable attention as light-harvesting units in inter- [12] and intramolecular [13][14][15][16][17] photocatalyst systems for light-driven proton reduction. In a study of dye-sensitised TiO2/Pt systems, Eisenberg and McCamant showed that incorporation of heavy atoms such as bromine or iodine at the 2,6 position of the BODIPY results in a pronounced coupling between singlet and triplet states that greatly decreases fluorescence quantum yield and fluorescence lifetime compared to the parent halogen-free compound and results in a more active photosensitizer [12].…”
Section: Introductionmentioning
confidence: 99%
“…7--12 Recently, several groups have published articles featuring dyads, in which Bodipy chromophores have been covalently bound to Co(dmg) 2 catalysts for application in solar energy conversion. [13][14][15][16][17] In these cases, the Bodipy contains a pyridine aryl group, which coordinates to Co(III) as a ligand on the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…18 The TONs with respect to chromophore reported 18 were greater than those reported for the earlier dyads. 15,16 Here, we present the results of a series of discrete Bodipy chromophores and the Co(dmg) 2 catalyst, in which the effects of halogenation, sterics, and component concentrations are examined. By optimizing the relative concentrations of the dye and catalyst we show that the system is strongly inhibited under conditions of excess catalyst, as was used in prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Cobaloximes have also been incorporated into heterogeneous systems such as glassy carbon, 20 nickel oxide, 21 carbon nanotubes, 22 and gallium phosphide 23,24 substrates. Furthermore, cobaloximes have been explored in conjunction with homogeneous photosensitizers, [25][26][27][28] as components in aqueous systems, [29][30][31] as a functional catalyst on vesicle membrane surfaces, 32 and used as part of an artificial hydrogenase in a hybrid SwMb system. 33 Moreover, increasingly elaborate ligand designs have been devised and studied.…”
Section: Introductionmentioning
confidence: 99%